Quantitative analysis of the cell‐surface roughness and viscoelasticity for breast cancer cells discrimination using atomic force microscopy. Issue 6 (11th January 2016) - Wang, Yuhua; Xu, Chaoxian; Jiang, Ningcheng; Zheng, Liqin; Zeng, Jinshu; Qiu, Caimin; Yang, Hongqin; Xie, Shusen
Summary: Breast cancer has been one of the most common malignant tumors threatening female health with high incidence. Cell mechanics is becoming an important issue and could serves as a potential indicator for early cancer diagnosis. In this study, atomic force microscopy (AFM) was applied to characterize and compare the surface nanostructure and viscoelasticity of different breast cell lines. Our results show that breast cancerous cells MCF‐7 exhibit more disorganized filamentous cytoskeleton structure with increased membrane roughness compared to benign breast cells MCF‐10A ( P < 0.05). The viscoelastic properties, including elasticity and viscosity, are significantly different between the two cell lines. MCF‐7 displays reduced elasticity and viscosity, indicating that breast cancer cells are softer and more fluid than benign counterpart. Our findings provide new insights into the biophysical changes of cells during tumor transformation and suggest it could be used for early cancer detection at single cell level. SCANNING 38:558–563, 2016. © 2016 Wiley Periodicals, Inc.